PHENOLIC COMPOSITION, ANTIOXIDANT CAPACITY OF SALVIA VERTICCILATA AND EFFECT ON MULTIDRUG RESISTANT BACTERIA BY FLOW-CYTOMETRY - Tekeli, Yener; Karpuz, Esra; Danahaliloglu, Hatice; Bucak, Serbay; Guzel, Yelda; Erdmann, Helmut (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Antioxidants are of great importance for preventing oxidative stress that may cause several degenerative diseases. Studies have indicated phytochemicals have high free-radical scavenging activity, which helps to reduce the risk of chronic diseases. The aim of the present study is the determination of antioxidant properties, polyphenolic content and multidrug resistant bacteria of Salvia verticcilata L. Materials and Methods: Methanol was used as the extraction solvent. The total phenolic content was calculated using Folin-Ciocalteau method and phenolic composition was determined by HPLC. The radical scavenging activity of plant was evaluated in vitro based on the reduction of the stable DPPH free radical. The reducing capacity was identified by using the FRAP method. The ability of Salvia verticcilata L. to increase the permeability of multidrug resistant bacterial cells was conducted by flow cytometric assay on Listeria innocua and E-coli. Results: The amount of total phenolics was found to be 347.5 mg GA/g extract. The IC50 value and FRAP assay are 0.61, and 0.944 respectively, Free radical scavenging effect and FRAP values are less than synthetic antioxidant compounds (BHA and BHT). Eight phenolic compounds were found in Salvia verticcilata L. Intense concentration of S. verticcilata L. has destroyed 97 % of living cells for Listeria innocua and 94.86% for E-coli Conclusion: This studyshows that methanolic extracts of Salvia verticcilata L. is a potential source of natural antioxidants and antimicrobial agent and can form the basis for pharmacological studies.